Method for synthesizing nano barium titanate
By using micro-scale reactors and microwave solid-phase sintering technology during barium titanate synthesis, the problems of uneven particle size and high cost caused by high temperature calcination in traditional methods are solved, and low-cost and high-efficiency nanotitanic acid are achieved Barium preparation.
Patent Information
- Application Number
- CN202411803938.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-02-18
AI Technical Summary
The traditional barium titanate synthesis method requires high temperature calcination, resulting in large particle size, poor uniformity, high cost and complex process, and there is a problem of impurity residue.
The material mixing is carried out by using a micro-scale reactor, and the titanium element is recovered through alkaline lysis and pickling. Combined with microwave solid-phase sintering technology, the reaction conditions are regulated to achieve the synthesis of nano-scale barium titanate.
It has achieved low-cost, uniform particle size and good dispersion preparation of nanobarium titanate. The average particle size of the product is 85nm and 96-99% purity, and has a wide range of potential for electronic ceramics and photoelectric catalytic applications.
Smart Images

Figure CN119461468A_ABST
Abstract
Description
Technical Field
[0001] The invention provides a method for synthesizing nano-barium titanate, belonging to the technical field of nano-material synthesis. Background Art
[0002] Due to its good dielectric, ferroelectric, piezoelectric and semiconductor properties, barium titanate is widely used in electronic components such as multilayer electronic ceramics (MLCC), thermistors (PTC), optoelectronic devices and various random access memories, and is known as the "cornerstone of electronic ceramics." The ideal barium titanate powder must have the advantages of high purity, fine particles and strong stability.
[0003] The patent (CN117185343A) discloses a method for synthesizing ultrafine barium titanate powder by solid phase method. The researchers used anatase phase TiO2 and BaCO3 as raw materials, ground and mixed them in a ball mill without adding dispersant, dried and sieved them, and then calcined them at 900-1100℃ to obtain barium titanate powder with a particle size of less than 300nm.
[0004] The patent (CN109369173A) discloses a method for preparing barium titanate powder, which discloses that titanium dioxide and barium carbonate are used as raw materials, the two raw materials are mixed and then ceramic materials such as SiC, ZrO2, Al2O3 are added, the mass of the ceramic material accounts for 5 to 90% of the total mass of the mixed powder, and after mixing, microwave solid phase sintering treatment is performed to finally obtain barium titanate powder with a particle size of 400nm.
[0005] The patent (CN1935635A) discloses a production process of nano-barium titanate, which adopts a chemical precipitation method with titanium tetrachloride and barium chloride as raw materials, oxalic acid as a precipitant, and by adding hydrolyzed polymaleic anhydride, hydroxyethylidene diphosphoric acid and maleic acid-acrylic acid copolymer as a dispersant, and preparing 300-400nm barium titanate powder through secondary calcination and ball milling.
[0006] The patent (CN104446445A) provides a method for preparing monodisperse barium titanate nanopowders. The researchers used the sol-gel method to prepare different forms of Ti(OH)4 gels with TiCl4 as the raw material, mixed them with Ba(OH)2 for reaction, and washed and dried the reactants to obtain monodisperse barium titanate nanopowder particles, which were finally transformed from cubic phase to tetragonal phase by low-temperature calcination.
[0007] There are many methods for synthesizing barium titanate at present. However, the traditional solid phase method, chemical precipitation method, and sol-gel method all require high-temperature calcination. At high temperatures, the products often agglomerate, and the powder particle size is large and the uniformity is poor. Similarly, problems such as high cost, complex process, and residual impurities also need to be solved. Therefore, it is particularly important to develop a low-cost method for preparing nano-scale barium titanate with excellent product performance. Summary of the invention
[0008] In view of this, the purpose of the present invention is to provide a method for synthesizing nano-barium titanate. The present invention is a method for synthesizing nano-barium titanate with low cost, uniform product particle size and good dispersibility, and the reaction conditions can be regulated according to the crystallization mechanism and growth mechanism of the reaction, thereby achieving the regulation of the morphology and performance of the product.
[0009] The present invention is achieved by adopting the following technical solutions:
[0010] A method for synthesizing nano-barium titanate comprises the following steps:
[0011] (1) mixing an alkali solution with a scrapped denitration catalyst powder and adding the mixture to a microscale reactor to achieve full mixing of the materials, then adding the mixture to a closed reactor, reacting at 80 to 150° C. for 2 to 10 hours, maintaining mechanical stirring during the process, and filtering, washing, and drying after the reaction to obtain a solid phase titanate powder;
[0012] (2) mixing the acid solution with the solid phase titanate powder of step (1), heating at 60-100° C. for 2-10 h, maintaining mechanical stirring during the process, filtering, washing, and drying after cooling to obtain metatitanate powder;
[0013] (3) mixing and stirring the metatitanate powder and deionized water to obtain a titanium source precursor suspension;
[0014] (4) dissolving a barium source in deionized water and stirring to obtain a barium source precursor solution;
[0015] (5) mixing the titanium source precursor solution of step (3) and the barium source precursor solution of step (4) at a titanium to barium molar ratio of 1:0.8 to 5, and adding the mixture to a microscale reactor to allow the materials to fully contact each other, thereby obtaining a mixed solution;
[0016] (6) Adding an inorganic base to the mixed solution in step (5) to adjust the pH value to ≥ 13, and then stirring the mixture at a temperature of 180 to 350° C. for 12 to 48 hours. After the reaction, washing with acetic acid solution, deionized water, and ethanol in sequence, and finally drying and grinding to obtain barium titanate powder.
[0017] Preferably, the concentration of the alkali solution in step (1) is 5 to 20 mol / L; the solid-liquid ratio of the alkali solution to the scrapped denitration catalyst powder is 1:5 to 30 g / mL.
[0018] Preferably, the concentration of the acid solution in step (2) is 2 to 15 mol / L; the solid-liquid ratio of the acid solution to the titanate powder is 1:5 to 30 g / mL.
[0019] Preferably, the solid-to-liquid ratio of the titanate powder and deionized water in step (3) is 1:10-20 g / mL.
[0020] Preferably, the concentration of the barium source precursor solution in step (4) is 2 to 4 mol / L.
[0021] Preferably, in step (5), the titanium source precursor solution and the barium source precursor solution are mixed at a titanium to barium molar ratio of 1:1 to 3.
[0022] Preferably, the inorganic base in step (6) is any one of sodium hydroxide, potassium hydroxide and ammonia water.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] In the present invention, a microscale reactor is used to pretreat the reaction materials. Its basic structure is as follows Figure 2 As shown, the microscale reactor consists of a stator and a rotor, wherein the surface of the stator has transverse thread-shaped grooves, the surface of the rotor has wedge-shaped serrations, and the size of the slit between the stator and the rotor is 0.2-1.5 mm, and the width of the slit between the stator and the rotor can be controlled by adjusting the rotor. The working principle of the reactor is to use a motor to drive the rotor to perform a relative high-speed rotational motion with a matching stator. During this process, the rotor rotates at a high speed, while the stator remains stationary. The material circulates between the stator and the rotor, and is subjected to strong shear force, friction force, high-frequency vibration and other physical effects to achieve efficient mixing of the material. The present invention uses scrapped denitration catalyst as a raw material, recovers the titanium element in the form of metatitanic acid through alkaline hydrolysis and acid washing, and uses it as a titanium source for synthesizing barium titanate, which greatly reduces the cost of raw materials. The barium titanate product prepared by the present invention has an axial ratio c / a=1.0070-1.0085, a tetragonal phase content of 60-85%, an average particle size of 85nm, and a purity of 96-99%, and has the potential for wide application in the fields of electronic ceramics and photoelectrocatalysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a process flow chart of the preparation method of synthesizing tetragonal barium titanate of the present invention;
[0026] Figure 2 is a schematic diagram of the structure of a microscale reactor;
[0027] Figure 3 It is the XRD diffraction pattern of the barium titanate powder prepared in Examples 1 to 4 of the present invention and Comparative Examples 1 to 2;
[0028] Figure 4 This is a SEM morphology image of the tetragonal barium titanate powder prepared in Example 1 of the present invention;
[0029] Figure 5 This is a SEM morphology image of the tetragonal barium titanate powder prepared in Example 2 of the present invention;
[0030] Figure 6 This is a SEM morphology image of the tetragonal barium titanate powder prepared in Example 3 of the present invention;
[0031] Figure 7 is a SEM morphology image of the tetragonal barium titanate powder prepared in Example 4 of the present invention;
[0032] Figure 8 This is a SEM morphology of the tetragonal barium titanate powder prepared in Comparative Example 1;
[0033] Fig. 9 This is the SEM morphology of the tetragonal barium titanate powder prepared in Comparative Example 2. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical scheme and advantages of the present invention clearer, the preferred embodiments of the present invention are further described in detail in conjunction with the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Example 1
[0036] A method for preparing tetragonal barium titanate powder, the specific steps are as follows:
[0037] (1) A sodium hydroxide solution with a concentration of 10 mol / L and a scrapped denitration catalyst powder were mixed at a solid-liquid ratio of 1:8 g / mL and added to a microscale reactor to achieve full mixing of the materials. The mixture was then added to a closed reactor and reacted at 150° C. for 4 h. Mechanical stirring was maintained during the reaction. After the reaction was completed, the solid phase titanate powder was filtered, washed, and dried;
[0038] (2) preparing a 4.5 mol / L hydrochloric acid aqueous solution and mixing it with the solid phase titanate powder described in step (1), heating it at 100° C. for 2 h, maintaining mechanical stirring during the process, filtering, washing, and drying after cooling to obtain metatitanic acid powder, and testing it by microwave digestion combined with ICP-OES, the sample purity was 99.3%;
[0039] (3) mixing the metatitanate powder and deionized water at a solid-liquid ratio of 1:5 g / mL to obtain a titanium source precursor suspension;
[0040] (4) dissolving the barium source in deionized water and stirring to obtain a barium source precursor solution with a concentration of 2 mol / L;
[0041] (5) mixing the titanium source precursor solution and the barium source precursor solution at a titanium-barium molar ratio of 1:1.5, and adding the mixture to a microscale reactor to allow the materials to fully contact each other, thereby obtaining a mixed solution;
[0042] (6) Ammonia water was added to the mixed solution to adjust the pH value to 14, and then the mixture was stirred and reacted at 200° C. for 24 hours with a stirring rate of 500 rpm. After the reaction, the mixture was filtered, washed with 5% acetic acid solution, deionized water, and ethanol in sequence, dried at 80° C. for 12 hours, and then ground to obtain barium titanate powder.
[0043] The X-ray diffraction pattern of the barium titanate powder obtained in Example 1 is as follows: Figure 3 As shown in (a), it can be seen from the figure that a split peak trend appears at the diffraction angle 2θ=45°, and the peak positions of the samples all correspond to the tetragonal phase BaTiO3 (PDF No.75-0462). The synthesized sample c / a=1.0070, the tetragonal phase content is 60%, and the sample purity is 98.8% after microwave digestion combined with ICP-OES testing.
[0044] The microscopic morphology and particle size distribution of the barium titanate powder obtained in Example 1 are shown in Figure 4 As shown, the morphology of the prepared BaTiO3 particles was analyzed using a scanning electron microscope. The prepared tetragonal BaTiO3 particles were cubic, with a particle size of about 80 nm, uniform particle size distribution, and uniform morphology.
[0045] Example 2
[0046] A method for preparing tetragonal barium titanate powder, the specific steps are as follows:
[0047] (1) A sodium hydroxide solution with a concentration of 10 mol / L and a scrapped denitration catalyst powder were mixed at a solid-liquid ratio of 1:8 g / mL and added to a microscale reactor to achieve full mixing of the materials. The mixture was then added to a closed reactor and reacted at 150° C. for 4 h. Mechanical stirring was maintained during the reaction. After the reaction was completed, the solid phase titanate powder was filtered, washed, and dried;
[0048] (2) preparing a 4.5 mol / L hydrochloric acid aqueous solution and mixing it with the solid phase titanate powder described in step (1), heating it at 100° C. for 2 h, maintaining mechanical stirring during the process, filtering, washing, and drying after cooling to obtain metatitanic acid powder, and testing it by microwave digestion combined with ICP-OES, the sample purity was 99.3%;
[0049] (3) mixing the metatitanate powder and deionized water at a solid-liquid ratio of 1:5 g / mL to obtain a titanium source precursor suspension;
[0050] (4) dissolving the barium source in deionized water and stirring to obtain a barium source precursor solution with a concentration of 2 mol / L;
[0051] (5) mixing the titanium source precursor solution and the barium source precursor solution at a titanium-barium molar ratio of 1:2, and adding the mixture to a microscale reactor to allow the materials to fully contact each other, thereby obtaining a mixed solution;
[0052] (6) Ammonia water was added to the mixed solution to adjust the pH value to 14, and then the mixture was stirred at 200° C. for 24 h with a stirring rate of 500 rpm. After the reaction, the mixture was filtered, washed with 5% acetic acid solution, deionized water, and ethanol in sequence, dried at 80° C. for 12 h, and then ground to obtain barium titanate powder. After microwave digestion combined with ICP-OES testing, the sample purity was 98.6%.
[0053] The X-ray diffraction pattern of the barium titanate powder obtained in Example 2 is as follows: Figure 3 As shown in (b), it can be seen from the figure that a relatively obvious split peak structure appears at the diffraction angle 2θ=45°, and the peak positions of the samples all correspond to the tetragonal phase BaTiO3 (PDF No.75-0462). The synthesized sample c / a=1.0075, and the tetragonal phase content is 65%, indicating that increasing the barium-titanium ratio is beneficial to the formation of tetragonal phase BaTiO3.
[0054] The microscopic morphology and particle size distribution of the barium titanate powder obtained in Example 2 are shown in Figure 5 As shown, the morphology of the prepared BaTiO3 particles was analyzed using a scanning electron microscope. The prepared tetragonal BaTiO3 particles showed a cubic morphology, the average particle size of the powder was about 88nm, the particle size distribution was relatively uniform, and the morphology was uniform.
[0055] Example 3
[0056] A method for preparing tetragonal barium titanate powder, the specific steps are as follows:
[0057] (1) A sodium hydroxide solution with a concentration of 10 mol / L and a scrapped denitration catalyst powder were mixed at a solid-liquid ratio of 1:8 g / mL and added to a microscale reactor to achieve full mixing of the materials. The mixture was then added to a closed reactor and reacted at 150° C. for 4 h. Mechanical stirring was maintained during the reaction. After the reaction was completed, the solid phase titanate powder was filtered, washed, and dried;
[0058] (2) preparing a 4.5 mol / L hydrochloric acid aqueous solution and mixing it with the solid phase titanate powder described in step (1), heating it at 100° C. for 2 h, maintaining mechanical stirring during the process, filtering, washing, and drying after cooling to obtain metatitanic acid powder, and testing the sample by microwave digestion combined with ICP-OES, the purity of the sample was 99.5%;
[0059] (3) mixing the metatitanate powder and deionized water at a solid-liquid ratio of 1:5 g / mL to obtain a titanium source precursor suspension;
[0060] (4) dissolving the barium source in deionized water and stirring to obtain a barium source precursor solution with a concentration of 2 mol / L;
[0061] (5) mixing the titanium source precursor solution and the barium source precursor solution at a titanium-barium molar ratio of 1:2, and adding the mixture to a microscale reactor to allow the materials to fully contact each other, thereby obtaining a mixed solution;
[0062] (6) Ammonia water was added to the mixed solution to adjust the pH value to 14, and then the mixture was stirred at 220° C. for 24 h with a stirring rate of 500 rpm. After the reaction, the mixture was filtered, washed with 5% acetic acid solution, deionized water, and ethanol in sequence, dried at 80° C. for 12 h, and then ground to obtain barium titanate powder. After microwave digestion and ICP-OES testing, the sample purity was 98.9%.
[0063] The X-ray diffraction pattern of the barium titanate powder obtained in Example 3 is as follows: Figure 3 As shown in (c), it can be seen from the figure that an obvious split peak structure appears at the diffraction angle 2θ=45°, and the peak positions of the samples all correspond to the tetragonal phase BaTiO3 (PDFNo.75-0462). The synthesized sample c / a=1.0080, and the tetragonal phase content is 78%, indicating that extending the reaction time is beneficial to the formation of tetragonal phase BaTiO3.
[0064] The microscopic morphology and particle size distribution of the barium titanate powder obtained in Example 3 are shown in Figure 6 As shown, the morphology of the prepared BaTiO3 particles was analyzed using a scanning electron microscope. The prepared tetragonal BaTiO3 particles showed a cubic morphology, and the average particle size of the powder was about 112nm. However, due to the short reaction time and incomplete crystal development, the particle size distribution was uneven.
[0065] Example 4
[0066] A method for preparing tetragonal barium titanate powder, the specific steps are as follows:
[0067] (1) A sodium hydroxide solution with a concentration of 10 mol / L and a scrapped denitration catalyst powder were mixed at a solid-liquid ratio of 1:8 g / mL and added to a microscale reactor to achieve full mixing of the materials. The mixture was then added to a closed reactor and reacted at 150° C. for 4 h. Mechanical stirring was maintained during the reaction. After the reaction was completed, the solid phase titanate powder was filtered, washed, and dried;
[0068] (2) preparing a 4.5 mol / L hydrochloric acid aqueous solution and mixing it with the solid phase titanate powder described in step (1), heating it at 100° C. for 2 h, maintaining mechanical stirring during the process, filtering, washing, and drying after cooling to obtain metatitanic acid powder, and testing the sample by microwave digestion combined with ICP-OES, the purity of the sample was 99.5%;
[0069] (3) mixing the metatitanate powder and deionized water at a solid-liquid ratio of 1:5 g / mL to obtain a titanium source precursor suspension;
[0070] (4) dissolving the barium source in deionized water and stirring to obtain a barium source precursor solution with a concentration of 2 mol / L;
[0071] (5) mixing the titanium source precursor solution and the barium source precursor solution at a titanium-barium molar ratio of 1:2, and adding the mixture to a microscale reactor to allow the materials to fully contact each other, thereby obtaining a mixed solution;
[0072] (6) Ammonia water was added to the mixed solution to adjust the pH value to 14, and then the mixture was stirred at 220° C. for 48 h with a stirring rate of 500 rpm. After the reaction, the mixture was filtered, washed with 5 wt % acetic acid solution, deionized water, and ethanol in sequence, dried at 80° C. for 12 h, and then ground to obtain barium titanate powder. After microwave digestion and ICP-OES testing, the sample purity was 99.0%.
[0073] The X-ray diffraction pattern of the barium titanate powder obtained in Example 4 is as follows: Figure 3 As shown in (d), it can be seen from the figure that an obvious split peak structure appears at the diffraction angle 2θ=45°, and the peak positions of the samples all correspond to the tetragonal phase BaTiO3 (PDFNo.75-0462). The synthesized sample c / a=1.0085, and the tetragonal phase content is 85%.
[0074] The microscopic morphology and particle size distribution of the barium titanate powder obtained in Example 4 are shown in Figure 7As shown, the morphology of the prepared BaTiO3 particles was analyzed using a scanning electron microscope. Due to the extension of the reaction time, the prepared tetragonal BaTiO3 particles showed a cubic morphology, the average particle size of the powder was 82nm, and the morphology was relatively uniform.
[0075] Comparative Example 1
[0076] A method for preparing tetragonal barium titanate powder, the preparation method of which is different from that in Example 2 only in that commercially available metatitanic acid is used as a raw material.
[0077] The X-ray diffraction pattern of the barium titanate powder obtained in Comparative Example 1 is as follows: Figure 3 As shown in (e), it can be seen from the figure that at the diffraction angle 2θ=45°, the diffraction peak has a split peak trend but it is not obvious. The peak position of the sample corresponds to the tetragonal BaTiO3 (PDFNo.79-2264), indicating that there is tetragonal BaTiO3 in the sample, but the content is low. The synthesized sample c / a=1.0064, the tetragonal phase content is 40%, and the sample purity is 98.8% after microwave digestion combined with ICP-OES testing.
[0078] The microscopic morphology and particle size distribution of the barium titanate powder obtained in Comparative Example 1 are shown in Figure 8 As shown, the morphology of the prepared BaTiO3 particles was analyzed using a scanning electron microscope. The average particle size of the prepared BaTiO3 product particles was about 100 nm, with obvious agglomeration and uneven particle size distribution.
[0079] Comparative Example 2
[0080] A method for preparing tetragonal barium titanate powder, the preparation method of which is different from that in Example 3 only in that a microscale reactor is not used to mix the materials.
[0081] The X-ray diffraction pattern of the barium titanate powder obtained in Comparative Example 2 is as follows: Figure 3 As shown in (f), it can be seen from the figure that there is no split peak structure in the diffraction peak at the diffraction angle 2θ=45°, and the peak position of the sample corresponds to the cubic phase BaTiO3 (PDFNo.79-2263), indicating that there is no tetragonal crystal phase of BaTiO3 in the sample.
[0082] The microscopic morphology and particle size distribution of the barium titanate powder obtained in Comparative Example 2 are shown in Fig. 9As shown, the morphology of the prepared BaTiO3 particles was analyzed by scanning electron microscopy. The average particle size of the prepared BaTiO3 product particles was about 395nm, with obvious agglomeration and very uneven particle size distribution. Compared with Example 3, it is shown that the use of a microscale reactor to process the material can achieve efficient mixing of titanium and barium precursors, which is beneficial to the transformation of the unit cell from a cubic phase structure to a tetragonal phase structure, and at the same time can optimize the dispersion of the product so that the product particle size is evenly distributed.
[0083] The present invention uses alkaline hydrolysis and acid washing methods to recover the titanium element in the scrapped denitration catalyst in the form of metatitanic acid, and uses this as a titanium source for synthesizing tetragonal barium titanate. After mixing with a barium source in a certain ratio, a microscale reactor is used for mixing treatment to successfully synthesize a nano tetragonal barium titanate product. The present invention has the characteristics of short process, low cost, high efficiency, etc. The test characterization results show that the prepared barium titanate product has an axial ratio c / a=1.0070-1.0085, a tetragonal phase content of 60-85%, an average particle size of 85nm, and a purity of 96-99%, and has a wide range of electronic ceramics and piezoelectric catalytic application potential.
[0084] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A method for synthesizing nano-barium titanate, characterized in that: The following steps are involved: (1) mixing an alkali solution with a scrapped denitration catalyst powder and adding the mixture to a microscale reactor to achieve full mixing of the materials, then adding the mixture to a closed reactor, reacting at 80 to 150° C. for 2 to 10 hours, maintaining mechanical stirring during the process, and filtering, washing, and drying after the reaction to obtain a solid titanate powder; (2) mixing the acid solution with the solid titanate powder of step (1), heating at 60-100° C. for 2-10 h, maintaining mechanical stirring during the process, filtering, washing, and drying after cooling to obtain metatitanate powder; (3) fully stirring and mixing the metatitanate powder described in step (2) with deionized water to obtain a titanium source precursor suspension; (4) dissolving a barium source in deionized water and stirring uniformly to obtain a barium source precursor solution; (5) mixing the titanium source precursor solution of step (3) and the barium source precursor solution of step (4) at a titanium to barium molar ratio of 1:0.8 to 5, and adding the mixture to a microscale reactor to allow the materials to fully contact each other, thereby obtaining a mixed solution; (6) Adding an inorganic base to the mixed solution of step (5) to adjust the pH value to ≥ 13, and then stirring the mixture at a temperature of 180 to 350° C. for 8 to 48 hours. After the reaction, washing with acetic acid solution, deionized water, and ethanol in sequence, and finally drying and grinding to obtain barium titanate powder.
2. The method for synthesizing nano-barium titanate according to claim 1, characterized in that: The concentration of the alkali solution in step (1) is 5 to 20 mol / L; the solid-liquid ratio of the alkali solution to the scrapped denitration catalyst powder is 1:5 to 30 g / mL.
3. The method for synthesizing nano-barium titanate according to claim 1, characterized in that: The concentration of the acid solution in step (2) is 2 to 15 mol / L; the solid-liquid ratio of the acid solution to the titanate powder is 1:5 to 30 g / mL.
4. The method for synthesizing nano-barium titanate according to claim 1, characterized in that: The metatitanic acid powder obtained in step (2) is tested by microwave digestion combined with ICP-OES, and the purity is 97-99.5%.
5. The method for synthesizing nano-barium titanate according to claim 1, characterized in that: In step (3), the solid-to-liquid ratio of the titanate powder to deionized water is 1:5-30 g / mL.
6. The method for synthesizing nano-barium titanate according to claim 1, characterized in that: The concentration of the barium source precursor solution in step (4) is 1 to 4 mol / L.
7. The method for synthesizing nano-barium titanate according to claim 1, characterized in that: The inorganic base in step (6) is any one of sodium hydroxide, potassium hydroxide, sodium carbonate and ammonia water or a mixture of them.
8. The method for synthesizing nano-barium titanate according to claim 1, characterized in that: The nano-tetragonal barium titanate powder synthesized in step (6) is tested by microwave digestion combined with ICP-OES, and the purity is 96-99%.
Citation Information
Patent Citations
Preparation method of monodisperse nano-powdery barium titanate
CN104446445A
Preparation method and product of tetragonal barium titanate powder
CN109369173A
Method for preparing superfine tetragonal-phase barium titanate powder by solid-phase method
CN117185343A
Process for producing nano barium titanate
CN1935635A